2010
DOI: 10.1038/ismej.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of a crenarchaeotal subcluster related to Candidatus Nitrosopumilus maritimus to ammonia oxidation in the suboxic zone of the central Baltic Sea

Abstract: Marine pelagic redoxclines are areas of enhanced biogeochemical cycling inhabited by distinct functional groups of prokaryotes. In this study, the diversity and abundance of archaeal and bacterial nitrifying populations throughout a pelagic redoxcline in the central Baltic Sea were examined using a suite of molecular methods. 16S rRNA/rRNA gene as well as bacterial and archaeal amoA mRNA/amoA gene fingerprints and clone libraries revealed that the putative nitrifying assemblages consisted solely of one crenarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
110
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 59 publications
13
110
0
Order By: Relevance
“…Assuming one amoA gene per genome (Walker et al, 2010;Blainey et al, 2011) and that one transcript is present per active cell, only 4% (median, 3%; range, 0.05-18%) of cells (1 in 25) were expressing the gene when sampled. Quantitatively, this percentage of 'active' cells seems low but is remarkably consistent with transcript data from the suboxic zone of the Baltic Sea (Labrenz et al, 2010) and the meso-and bathypelagic zones of the oligotrophic Pacific Ocean (Church et al, 2010). However, if only the amoA-expressing cells were active, these 'active' members of the AOA community would have to be oxidizing ammonia at a rate of 886 fmol cell À 1 d À 1 , several orders of magnitude higher than other published estimates, which range from 0.2-13 fmol cell À 1 d À 1 (Wuchter et al, 2006;Martens-Habbena et al, 2009;Santoro et al, 2010;2011).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Assuming one amoA gene per genome (Walker et al, 2010;Blainey et al, 2011) and that one transcript is present per active cell, only 4% (median, 3%; range, 0.05-18%) of cells (1 in 25) were expressing the gene when sampled. Quantitatively, this percentage of 'active' cells seems low but is remarkably consistent with transcript data from the suboxic zone of the Baltic Sea (Labrenz et al, 2010) and the meso-and bathypelagic zones of the oligotrophic Pacific Ocean (Church et al, 2010). However, if only the amoA-expressing cells were active, these 'active' members of the AOA community would have to be oxidizing ammonia at a rate of 886 fmol cell À 1 d À 1 , several orders of magnitude higher than other published estimates, which range from 0.2-13 fmol cell À 1 d À 1 (Wuchter et al, 2006;Martens-Habbena et al, 2009;Santoro et al, 2010;2011).…”
Section: Resultssupporting
confidence: 64%
“…The roles of WCA and WCB in nitrification Although there have been quantitative assessments of AOA amoA transcript abundances in the ocean, those published have focused on whole community activity, rather than ecotypes (Lam et al, 2007(Lam et al, , 2009Church et al, 2010;Labrenz et al, 2010). Considering the sum of WCA and WCB genes and transcripts to represent the total community of AOA in the water column (Beman et al, 2008), a consistent level of specific activity (transcript to gene ratio) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…This has also been reported in the Black Sea (Lam et al, 2007), the Baltic Sea (Labrenz et al, 2010) and in soil (Nicol et al, 2008), whereas in the North Pacific Ocean the mRNA transcripts were 10-500-fold more abundant than gene copies in the upper 200 m of the water column (Church et al, 2010).…”
Section: Expression Of Thaumarchaeal Nirk and Amoa In Monterey Baymentioning
confidence: 70%
“…The permeabilization of the cell walls turned out to be the most crucial for visualization of MCG. Archaeal cell walls are usually permeabilized either by a treatment with 10-15 mg ml À 1 proteinase K for 1-5 min, 0.5% SDS for 10 min at room temperature or with 60 U ml À 1 achromopeptidase at 37 1C (Teira et al, 2004;Knittel and Boetius, 2009;Labrenz et al, 2010). However, none of these methods was successful for the visualization of MCG.…”
Section: Quantification Of Mcg In Several Types Of Sedimentsmentioning
confidence: 99%